A 5-years review of antibiotic resistance of organism cultured from patients in husm nicu compared to other ICUS - Noorzaitun, Ariffin (2011)
Most of the infections in intensive care settings need to be treated empirically before the causative organism is known. The right choice of antibiotics is very important and can make the difference between life and death of the infected patient. On the other hand the overuse of broad spectrum antibiotics can lead to resistance. It is very important to know the resistance pattern in particular wards in order to make rational decisions for empirical therapy To determine and compare the bacterial demographics and antibiotic resistance pattern of bacteria in the neonatal intensive care unit (NICU) and ICU/HD (intensive care units /high dependency units) in HUSM (Hospital Universiti Sains Malaysia) This study is a retrospective descriptive study of organisms cultured from the NICU, HUSM, and their antibiotic resistance pattern over the last 5 years (2005-2009) compared to organisms (and their resistance pattern) grown from other intensive or high dependency care units in the same hospital during the same period. The file containing the positive cultures from each ward in HUSM was available in the archives of the Microbiology Laboratory of HUSM, Kubang Kerian. These data were cleaned base on admission date and antibiotic resistance and they were subsequently analyzed statistically using SPSS version 12.1. There were 6403 bacteria included in the study: 1320 from the NICU and 5083 from ICU/HDU. In the NICU 25.8% were cultured from early specimens and 74.2% from late specimens. In the ICU/HDU, 43.0% came from early and 57.0% from late specimens. In the ICU/HDU Gram negative bacteria were significantly more common than in the NICU. (60% vs. 49%, p < 0.001). The most common Gram negative organism cultured from the ICU/HDU was Acinetobacter spp. The most common one in the NICU was Klebsiella pneumoniae ss pneumonia. Among the common Gram negative organisms there were significant differences between the ICU/HDU and NICU. The most common Gram positive organism cultured from the ICU/HDU was Staphylococcus aureus (40.0 vs. 18.7%; p<O.OOl) and from the NICU was coagulase-negative staphylococci. (32.2 vs. 62.3%; p<O.OOI ). Regarding antibiotic resistance, it was significantly lower in the NICU, compared to other ICU/HDU. The most pronounced differences were found for Gram negative organisms cultured but also for Gram positive organisms there was a less pronounced lower resistance in the NICU.